Development of paper-gate transistor toward direct detection from microbiological fluids. (24th March 2017) - Kajisa, Taira; Sakata, Toshiya
Abstract: In this study, a paper-gate transistor was developed to detect glucose using an extended-gate field-effect transistor (FET). A filter paper was used as an extended gate electrode, in which Au nanoparticles (AuNPs) modified with phenylboronic acids (PBAs) were included. PBA–AuNPs play an important role as a support to not only be entrapped in cellulose fibrils but also bind to the targeted glucose in a paper. The surface properties of PBA–AuNPs were investigated to elucidate the electrical properties of the paper-gate electrode using an absorption spectrum and a zeta potential analysis. Moreover, the paper-gate electrode enabled us to detect glucose at the micromolar level on the basis of the principle of FET devices. A platform based on the paper-gate transistor is suitable for a highly sensitive system to detect glucose in trace samples such as tears, sweat, and saliva in the future.